Right Atrium Volume Index in Non-Severe Chronic Obstructive Pulmonary Disease - Cherneva Zh. (Sciendo, 2020)
Introduction: Right atrium volume index (RAVI) has recently been reported as a quantitative echocardiographic parameter associated with right ventricular systolic dys-function (RVSD) in patients with pulmonary arterial hypertension (PAH) due to chronic obstructive pulmonary disease (COPD).